A Blended ESP Learning Model Integrated with Digital Literacy - Si Putu Agung Ayu Pertiwi Dewi; Ni Komang Purwaningsih (International Journal of Education and Teaching Zone, 2026)
Contemporary nursing practice requires professionals to integrate English communication, nutritional literacy, and digital competence to support interdisciplinary healthcare. However, English for Specific Purposes (ESP) curricula often fail to address these competencies in an integrated manner. This study conducted a multidimensional needs analysis to identify the ESP learning materials and pedagogical approaches required to enhance nutritional awareness among undergraduate nursing students. A mixed-methods sequential explanatory design was employed with 46 nursing students in Bali, Indonesia. Data were collected through a 70-item questionnaire and semi-structured interviews and analyzed using quantitative and qualitative approaches. The findings revealed strong support for an ESP curriculum integrating nutrition and digital technology. Students identified limited mastery of medical and nutritional terminology as a major challenge affecting their ability to read scientific literature and communicate effectively in clinical settings. They also expressed a clear preference for blended learning because of its flexibility and interactive learning opportunities. These findings highlight the need for contextualized, technology-enhanced ESP materials that integrate language learning with professional nursing competencies. The study contributes practical guidance for designing ESP curricula that better prepare nursing students for digitally supported and internationally oriented healthcare practice.